The Role of Exercise in Treating Low Back Pain. Issue 8 (August 2022) - Essman, Matthew; Lin, Cindy Y.
Abstract : Appropriate exercise is an important part of the management of acute and chronic low back pain. This review describes the role of exercise for low back pain. Abstract: The purpose of this review is to highlight the role of exercise in preventing and managing acute and chronic axial low back pain (LBP). LBP is one of the leading contributors to years lived with disability as well as health care expenditures in the United States. With an expected increase in prevalence due to an aging population, sports medicine providers have a unique opportunity to provide effective treatment strategies incorporating exercise advice and prescription. Although the majority of individuals with acute LBP will have their symptoms resolve spontaneously, almost 40% will have recurrence or develop chronic LBP within 1 year. No single exercise method has been shown to be more effective than another. The evidence for walking programs, aerobic exercise, yoga, Pilates, and tai chi for LBP is discussed. Our review summarizes the beneficial role of a personalized exercise program and related counseling strategies in the prevention and management of LBP.